Analysis of the Malaysian Women's Policy Agency (WPA) network in the implementation of gender empowerment initiatives - Aminudin, Rabi'ah (Partridge, 2018)
The research touches on the issue of women not from cultural perspective, rather from administrative and institutional perspectives. In view of the increasing need for women empowerment in today's society, her study analyses Women Policy's Agency (WPA) in Malaysia, focusing on the Ministry of Women, Family, and Community Development and its institutional capacity to implement gender empowerment initiatives. The author demonstrates the variance of network and actors involved in relation to the WPA and the extent of their influence on the agency.